Proteomic profiling of mammalian COPII and COPI vesicles - Adolf, Frank; Rhiel, Manuel; Hellwig, Andrea; Béthune, Julien; Wieland, Felix T.; Gao, Qi (Cell reports, 2019)
Summary - Intracellular transport and homeostasis of the endomembrane system in eukaryotic cells depend on the formation and fusion of vesicular carriers. Coat protein complex (COP) II vesicles export newly synthesized secretory proteins from the endoplasmic reticulum (ER), whereas COPI vesicles facilitate traffic from the Golgi to the ER and intra-Golgi transport. Mammalian cells express various isoforms of COPII and COPI coat proteins. To investigate the roles of coat protein paralogs, we have combined in vitro vesicle reconstitution from semi-intact cells with SILAC-based mass spectrometric analysis. Here, we describe the core proteomes of mammalian COPII and COPI vesicles. Whereas the compositions of COPII vesicles reconstituted with various isoforms of the cargo-binding subunit Sec24 differ depending on the paralog used, all of the isoforms of the COPI coat produce COPI-coated vesicles with strikingly similar protein compositions.